Estudo Energético e Fisicoquimico do Carvão Vegetal de Eucalyptus dunnii Maiden - Scremin, André Luis Trentin (2015)
The Charcoal is an energetic source obtained through the wood carbonization process. The energetic potential of a vegetal biomass is rated from its heating power, followed by a chemical analysis for the levels of volatile materials, ashes and fix carbon in the biomass and in the Charcoal. The main goal of this work was to verify an influence of the final temperature of carbonization over the physical, chemical and energetic characteristics of the Charcoal from Eucalyptus dunnii. For the research 30 trees were used and in each tree a cylindrical sample of 50 cm were taken. These cylindrical samples were cut at the height related to the diameter at breast height (DBH), at 1.30 m above the ground level. From these cylinders were obtained the test pieces with the dimensions of 2x3x5 cm to be used in tests of carbonization. The bodies of the test piece were organized into five classes (22 - 29.1 (cm), 29.2 to 36.3 (cm), 36.4 to 43.5 (cm), 43.6 to 50.7 (cm) and 50.8 - 58 (cm)) in relation to (BH) the circumference at breast height. The test pieces were carbonized using 5 different temperatures of an furnace oven; 300°, 350°C, 400°C, 450° and 500°C under controlled conditions. The methodology used to analyze the chemical properties of the Charcoal (volatile materials, fix carbon and ashes) was the NBR 8112 from ABNT and the Model equipment SDT Q 600 was used to determine the thermogravimetry analyzes (TG) correlating the produced Charcoal with the original wood and the (DTA) in order to determine the superior heating power. The results showed there was no statistical difference in the wood`s density but just in the percentage of humidity among the classes. With the influence of the temperatures among the classes the chemical properties of the Charcoal differ statistically among the classes, temperatures and both factors. The class III in the temperature of 400°C shows higher heating power 21,99 MJ/Kg or 5253,89 Kcal/Kg. With the intent of reducing the experimental error, all analyzes were made in four different repetitions and the ASSISTAT version 7.6 beta program was used for the experimental lineation (2011).